Answer:
t = 36
Step-by-step explanation:
If one of the roots is "a", the equation can be factored as ...
(5x -a)(x -a) = 0
5x^2 -6ax +a^2 = 0
Comparing terms to the given equation, we see that ...
-6ax = -36x
a = 6 . . . . . . . . divide by -6
Then ...
a^2 = t
36 = t . . . . . . . substitute 6 for a
_____
The roots are 6 and 6/5.
Answer: look it up
Step-by-step explanation: Lollll
The equation would be x+3=y
nancy's age + three years= Jen's age
If 21 is added to (+ 21) a number (x) the result (=) is 40 less than (- 40) twice the number (2x)
x + 21 = 2x - 40 Add 40 to both sides
x + 61 = 2x Subtract x from both sides
61 = x Switch the sides to make it easier to read
x = 61